Improvement of MSME Sales and Capital Management through a Website-Based Marketplace System - Sanjaya, I Putu Sura; Sudana, Oka; Dharmaadi, I Putu Arya (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol. 9, No. 2, August 2021DO - 10.24843/JIM.2021.v09.i02.p01, 2021)
Micro, Small and Medium Enterprises (MSMEs) have a good enough potential to overcome poverty, because they have an absorption contribution of 99.45 percent. MSMEs can be developed by utilizing e-marketplaces, but the existing marketplaces have not been able to solve the problems faced by MSMEs. One of the problems faced by MSME actors is difficulty in accessing capital. In general, MSME capital is obtained from the bank, but MSME actors are burdened by the need for collateral to apply for loans. Based on these problems, a marketplace information system for MSME products was built with peer-to-peer lending features that can help MSMEs do product marketing as well as apply for loans on easy terms and without any collateral. Testing the system with the black box method shows that all features are functioning properly and in accordance with the expected functionality.Testing with the acceptance testing method for MSME actors obtained an average score of 89.25%, so it can be concluded that the system is acceptable and in accordance with the needs of MSME players in Gianyar Regency.